The Effect Of Management Accounting On Decision Making In Bank Sumut Aek Kanopan Branch, Labuhan Batu Utara Regency - Dinda Wulandari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2022)
This study aims to determine the effect of management accounting on decision making at Bank Sumut Aek Kanopan Branch, North Labuhan Batu Regency. The independent variable in this study is Management Accounting. The dependent variable in this study is decision making. This research uses population studies or census studies. The data in this study are primary data obtained from distributing questionnaires directly to all employees at Bank Sumut Aek Kanopan Branch, Labuhan Batu Utara Regency. The results of the study partially show that the application of management accounting at Bank Sumut, Aek Kanopan Branch, Labuhan Batu Utara Regency has a significant effect on decision making.